ICT AND MODERN FOREIGN LANGUAGES: LEARNING OPPORTUNITIES AND TRAINING NEEDS - Davies, Graham (International Journal of English Studies, 2002)
This article is divided into two main sections. The first section considers why technology has not lived up to its expectations in bringing about improvements in language learning. Many learning opportunities are offered by new technologies but they are not fully exploited, mainly owing to the lack of relevant training offered to teachers. In addition, with the advent of the Web, there is a disturbing trend towards removing the teacher from the learning process - which is simply not acceptable. The second section of the article looks at a website that offers a considerable volume of ICT training materials or language teachers, namely the ICT4LT website: http://www.ict4lt.org. The author examines the aims behind the site as a whole and the pattern of site visits, discussing the key issues and drawing conclusions based on an analysis of the pattern of visits to different modules of the site. Some important lessons have been learned regarding the type of training that teachers appear to need, for example: the continued interest in multimedia and the high demand for introductory courses. It is also evident that Web traffic is predominantly one-way and confined to certain sectors of the world, indicating that much more has to be done in order to stimulate discussion and to make the Web accessible to underserved regions of the world.